PENGUATAN KELEMBAGAAN KELOMPOK TANI SENGKANAUNG DI DESA AKEKOLANO KECAMATAN OBA UTARA KOTA TIDORE KEPULAUAN - Mila Fatmawati; Mardiyani Sidayat; Nurdiyanawati Djumadil; Fatmawati Kaddas; Natal Basuki; Haris Mahmud; Nursamsi Nursamsi; Khairun Annisa; Syahroni Syahroni (STKIP Persada Khatulistiwa Sintang, 2025)
ABSTRACTFarmer Institutions provide institutional strengthening of farmers through non-formal education that includes activities in knowledge and skills with the main objective of providing strengthening to farmers is one form of empowerment of farmers and agricultural business actors to increase productivity, income and welfare. In improving the knowledge and skills of the community in utilizing agricultural crops into crops that have high economic value. Assistance to farmers in Akekolano Village, Oba District is very important, especially in terms of institutional strengthening of this group, it is necessary to build public awareness in terms of cooperation between extension officers with farmers and other related institutions. The objects that are the main targets in institutional strengthening are farmer groups and the general public in Akekolano Village, Oba District. Where the targets are farmers and farmer group associations who are de facto the family economic managers and young men and women who come from farming families. Keywords: Institutions, Farmer Groups, Values, Economy and EmpowermentABSTRAKKelembagaan Petani memberikan penguatan kelembagaan kepada petani melalui pendidikan non formal yang meliputi kegiatan dalam pengetahuan dan ketrampilan dengan tujuan utama memberikan pengauatan kepada petani adalah salah satu bentuk upaya pemberdayaan petani dan pelaku usaha pertanian untuk meningkatkan produkstivitas, pendapatan dan kesejahteraan. Dalam meningkatkan pengetahuan dan keterampilan mayarakat dalam memanfaatkan tanaman pertanian menjadi tanaman yang memiliki nilai ekonomi tinggi. Pendampingan terhadap petani di Desa Akekolano Kecamatan Oba sangat penting terutama dalam hal penguatan kelembagaan kelompok ini perlu untuk membangun kesadaran masyarakat dalam hal kerjasama antar petugas penyuluh dengan petani serta lembaga terkait lainnya. Adapun objek yang menjadi target utama dalam penguatan kelembagaan yaitu kelompok petani serta masyarakat umum yang berada di Desa Akekolano Kecamatan Oba. Dimana sasarannya adalah para petani dan gabungan kelompok tani yang secara de facto merupakan pengatur ekonomi keluarga dan para pemuda/pemudi yang berasal dari keluarga petani.Kata Kunci: Kelembagaan, Kelompok Tani, Nilai, Ekonomi dan Pemberdayaan